2015
DOI: 10.1096/fj.14-258533
|View full text |Cite
|
Sign up to set email alerts
|

A20 suppresses vascular inflammation by recruiting proinflammatory signaling molecules to intracellular aggresomes

Abstract: A20 protects against pathologic vascular remodeling by inhibiting the inflammatory transcription factor NF-kB. A20's function has been attributed to ubiquitin editing of receptor-interacting protein 1 (RIP1) to influence activity/stability. The validity of this mechanism was tested using a murine model of transplant vasculopathy and human cells. Mouse C57BL/6 aortae transduced with adenoviruses containing A20 (or b-galactosidase as a control) were allografted into major histocompatibility complex-mismatched BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In our experimental conditions, A20 protein levels in WT cells increased by a factor of more than four following exposure to LPS‐nigericin, as revealed by immunoblotting and confirmed by immunofluorescence approaches (Figure c,d). This increase was associated with the appearance of intracellular A20‐positive punctate bodies, previously reported to correspond to insoluble aggresomes in which A20 sequesters inflammatory intermediates required for NF‐κB signaling (Enesa, Moll, Luong, Ferran, & Evans, ). The upregulation of A20 protein levels was accompanied by an upregulation of TNFAIP3 expression following exposure to LPS‐nigericin, as indicated by the quantitative analysis of transcript levels (Figure e).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In our experimental conditions, A20 protein levels in WT cells increased by a factor of more than four following exposure to LPS‐nigericin, as revealed by immunoblotting and confirmed by immunofluorescence approaches (Figure c,d). This increase was associated with the appearance of intracellular A20‐positive punctate bodies, previously reported to correspond to insoluble aggresomes in which A20 sequesters inflammatory intermediates required for NF‐κB signaling (Enesa, Moll, Luong, Ferran, & Evans, ). The upregulation of A20 protein levels was accompanied by an upregulation of TNFAIP3 expression following exposure to LPS‐nigericin, as indicated by the quantitative analysis of transcript levels (Figure e).…”
Section: Resultsmentioning
confidence: 73%
“…| 1745 sequesters inflammatory intermediates required for NF-jB signaling (Enesa, Moll, Luong, Ferran, & Evans, 2015). The upregulation of A20 protein levels was accompanied by an upregulation of TNFAIP3 expression following exposure to LPS-nigericin, as indicated by the quantitative analysis of transcript levels (Figure 4e).…”
Section: Mouton-liger Et Almentioning
confidence: 83%
“…APOA1, a major component of high density lipoprotein (HDL) in plasma [ 41 ], was positively associated with each of the three carotenoids, possibly reflecting shared lipoprotein transport or, co-existing antioxidant, anti-inflammatory and other metabolic functions [ 42 ]. On the other hand, TNIP1, an inhibitor of the pro-inflammatory transcription factor, NF-kB [ 43 , 44 ] was negatively correlated with all three carotenoids. We had also shown relative abundance of TNIP1 to be positively associated with the acute phase reactant, alpha-1-acid glycoprotein (AGP), or orosomucoid, in this population [ 27 ], explained by a negative feedback loop whereby TNIP1 is upregulated by inflammation in order to maintain immune homeostasis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A20 is a cytoplasmic seven zinc finger protein that was upregulated by NF-κB in most cell types, including hepatocytes 9 , 10 . The critical role of A20 in the regulation of inflammatory response through inhibition of NF-κB activation pathway has been well established 11 - 15 . Serial studies by Dr. Ferran and her colleagues suggested that despite inhibition of NF-κB activation, A20 exerted multiple hepatoprotective functions, including anti-apoptotic and pro-proliferative effects 10 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%